Screen for Child Anxiety Related Disorders (SCARED)-Child version: validity and reliability assessment among children aged 13-15 years - Sinha De Silva; Sudharshi Seneviratne; Dulani Samaranayake (College of Community Physicians of Sri Lanka, 2022)
Introduction: Anxiety disorders is one of the most prevalent psycho-pathological condition among children and adolescents. Screen for Anxiety Related Disorders (SCARED)-Child version is a cross-culturally validated self administered questionnaire to detect children with anxiety disorders.   Objectives: To assess the validity and reliability of SCARED-Child to identify anxiety among adolescents aged 13-15 years attending government schools (Sinhala medium) in the district of Colombo, Sri Lanka   Methods: The SCARED-Child was culturally adapted, translated to Sinhala and its judgmental validity was ensured. The instrument was validated among 423 adolescents aged 13-15 years in Colombo District by assessing criterion validity using the diagnosis made by a consultant psychiatrist as the gold standard, developing clinically validated cut-off values using ROC curve. The internal consistency and test-retest assessment were used to assess the reliability.   Results: The culturally adapted and translated SCARED-Child (Sinhala version) showed sensitivity of 85.7% (95% CI=74.61, 93.25) and specificity of 91.3% (95% CI=88.0, 94.07) at a cut-off of 36.5, with a high reliability of Cronbach's alpha (0.87) and test-retest correlation coefficient (0.74).   Conclusions & Recommendations: This study revealed that SCARED-Child has a high validity and excellent reliability to identify a child with an anxiety disorder at community setting.